2005
DOI: 10.1143/jjap.44.l405
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Lateral Overgrowth of High Al Composition AlGaN Alloys on Deep Grooved SiC Substrates

Abstract: Fully coalesced Al 0:93 Ga 0:07 N films were demonstrated by metalorganic chemical vapor deposition on deep grooved SiC substrates. Lateral Al 0:93 Ga 0:07 N growth was achieved at low V/III ratios during growth. The deep grooves enabled coalescence despite of parasitic growth in the trenches. Dislocation reduction in the overgrown regions of the films was observed by transition electron microscopy and atomic force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Maskless ELO by laterally overgrowing a trench instead of a mask material is an alternative avenue to reduce densities of both threading dislocations and cracks. ELO of AlN and high Al-molar fraction AlGaN such as Al 0.96 Ga 0.04 N on sapphire or SiC substrate have been reported by several groups [76,[81][82][83]. Significant reduction in TDD was observed in the areas between ridges.…”
Section: Epitaxial Lateral Overgrowth Of Aln and High Al-molar Fractimentioning
confidence: 70%
“…Maskless ELO by laterally overgrowing a trench instead of a mask material is an alternative avenue to reduce densities of both threading dislocations and cracks. ELO of AlN and high Al-molar fraction AlGaN such as Al 0.96 Ga 0.04 N on sapphire or SiC substrate have been reported by several groups [76,[81][82][83]. Significant reduction in TDD was observed in the areas between ridges.…”
Section: Epitaxial Lateral Overgrowth Of Aln and High Al-molar Fractimentioning
confidence: 70%
“…ELO of AlN and high Al-molar fraction AlGaN such as Al0.96Ga0.04N on sapphire or SiC substrate have been reported by several groups. [72,[77][78][79] Significant reduction in TDD was observed in the areas between ridges. A maximum output power of 2.7 mW under CW operation of 273 nm DUV LEDs on ELO AlN templates with the wing region having TDD of 3×10 8 cm -2 has been reported by Hirayama et al [80] By reducing the TDD in AlN layers on sapphire from 10 10 cm −2 to 10 9 cm −2 , output powers of 1mW and about 4mW for 295 nm and 324 nm LEDs, respectively, have been demonstrated by Kueller et al [69] This method has also been applied for growing AlN template on Si (111) substrate, as illustrated in Figure 7.…”
Section: Epitaxial Lateral Overgrowth Of Aln and High Al-molar Fractimentioning
confidence: 97%
“…The ELO growth for AlGaN films has been tried to reduce the dislocation density on sapphire substrates but has been unsuccessful due to the nucleation of polycrystals on the mask material [4]. Although several authors have reported the threading dislocation density reduction in the AlGaN films [1,5,6], the growth of high-quality AlGaN films with low dislocation density remains to be a difficult problem.…”
Section: Introductionmentioning
confidence: 99%